La versión Browning - Asquith, Anthony, 1902-1968 (Madrid Regasa films, 1951)
Andrew Crocker-Harris is an embittered and disliked teacher of Greek and Latin at a British public school. After nearly 20 years of service, he is being forced to retire on the pretext of ...
Basada en la obra de Terence Rattigan
Michael Redgrave, Jean Kent, Nigel Patrick
Reino Unido, 1951
No apta para menores de 12 años
Hablado en inglés. Subtítulos en inglés, español
Keywords: Películas cinematográficas -- DVD